Color atlas of immunocytochemistry in diagnostic cytology - Ganjei-Azar, Parvin; Nadji, Mehrdad (Springer, 2007)
"[This book] is a practical user-friendly volume that allows quick reference in the selection and interpretation of markers in specific differential diagnoses in the daily practice of diagnostic cytology. The atlas contains nearly 300 lavish illustrations in color."--Publisher's description, p. [4] of cover.